Promosi Dan Informasi Pada Media Video Profile SMA Mandiri Balaraja - Ria Wulandari; Achmad Rachmat; Bobby Aditya Nugraha (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2018)
Access to information is now a very important thing, because the information everyone will know. SMA Mandiri Balaraja has many facilities and and has different belacar way. SMA Mandiri Balaraja is an education that has the authority to promote SMA SMA Mandiri Balaraja tangerang district. Currently SMA Mandiri Balaraja not have a media information that explains in detail that can attract prospective students to register and recognize the existing facilities in SMA Mandiri Balaraja. This designed information and promotional video explains the excellence of learning, school facilities, extensive building, extracurricular activities at the present time, so it can be an attraction for prospective students and high school students of Balaraja Mandiri as well as the community, to find out information and promotion of SMA Mandiri Balaraja. The purpose of this study is to achieve the target of SMA Balaraja Mandiri High School in terms of conveying information and promotion about SMA Mandiri Balaraja, and increasing the number of prospective students and students who will enroll in SMA Mandiri Balaraja every year. The research methods used in this study include Data Collection, Media Design Analysis, and Concept Media Production (KPM) which includes: pre production, production, and post production. Through the media information and promotion SMA Mandiri Balaraja designed will be informed through: Youtube, SMA Mandiri Balaraja Website and facebook. The expected target is, prospective students and students who will enroll in SMA Mandiri Balaraja and the community can know SMA Balanganja Mandiri Tangerang district, and can increase the number of prospective students and girls who visit Balaraja Mandiri SMA every year.